THE RATIONAL USE OF RESOURCES IS A NECESSARY CONDITION FOR THE EFFECTIVE DEVELOPMENT OF PRODUCTION - Novikova, I. V. (Science and Transport Progress, 2008)
The problem of saving the resources in new conditions of management and economic establishing and growth of the Ukrainian industrial enterprises is studied. The role of scientific and technical progress in solving this problem is given.